Gmerki oraz pieczęcie herbowe mieszczan (uwagi w związku z odnalezieniem na terenie badań archeologicznych w Gdańsku przy ulicy 3 Maja dwóch nieznanych dotychczas zabytków sfragistyki mieszczańskiej o metryce XV- i XVI-wiecznej) = House Marks and The Coat of Arms of the Burghers (comments in connection with the discovery of two unknown sigillographic finds at excavation in Gdańsk at 3 Maja Street) - Bobowski, Bogdan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to indicate diversity of the Heraldic Seals and the House Marks as a completely different phenomena. House Marks served as signs of individuality-identity, chich labeled belongings, tools, houses, etc. They confirmed the quality and authenticity of the sold goods. Their popularity in different parts of Europe took place in the 16th and 17th century. The earliestHouse Marks in Poland have been noticed in the 14th century.
Keywords: sfragistyka; gmerk; herb; pieczęć herbowa; zabytki archeologiczne; sigillography; house mark; coat of arms; seal; archaeological artifacts